Highly operative NiO/ZnO nanocomposites for photocatalytic removal of azo dye. (December 2022) - Gnanasekaran, Lalitha; Chen, Wei-Hsin; Soto-Moscoso, Matias
Abstract: The far-reaching technology of semiconductors in treating water pollutants reduces serious health hazards to humans and other eco-systems. With this interpretation, this work is attempted for the first time to synthesize nanosized pristine NiO and ZnO materials, and NiO/ZnO (70:30, 50:50) composites by co-precipitation method. The synthesized materials were then portrayed for their properties using various instrumental techniques such as X-ray diffraction (XRD), Transmission electron microscope (TEM), Energy dispersive X-ray spectrum (EDXS), Fourier transform Infrared spectrum (FT-IR). The main approach of this work is connected with the ultra violet (UV) photocatalytic degradation of MO (methyl orange) by employing the synthesized nanomaterials as catalysts. In view of results, the photocatalytic degradation of NiO/ZnO (70:30) has reported the greatest efficiency than the other catalysts. This outcome lies with the consideration of higher content of NiO present in the composite than ZnO. Further, there was the existence of higher surface area analysed from the BET result. Also, the NiO/ZnO (50:50) sample showed lower degradation efficiency in terms of formed agglomeration when surveyed through TEM. Besides, the positive mechanism of photocatalysis reaction forms the essential hydroxyl radicals which correspond to MO degradation. Moreover, the highly efficient NiO/ZnO (70:30) sample has been trialled for photocatalytic repetition process to observe the stability of degradation. It has accounted with good efficiency for 5 repeated cycles. Finally for UV degradation, the recognized photocatalytic aspect was due to the surface morphology enhanced surface area, synergistic effects of metal oxides and electron-hole charge separation. Graphical abstract: Image 1 Highlights: The prepared nanocatalysts have great capabilities to reduce water contaminants. The result of recycling process showed that the prepared nanocatalyst exposed better stability. The prepared nanocatalysts exhibited mixed heterostructures.